International Labour Organization is 90 years: Vectors of Activities - D. K. Bekyashev (Московский журнал международного права)
The article is dedicated to the 90th anniversary of the International Labour Organization (ILO). It reviews concisely the history of its establishment, considers the legal status of this organization and the record of relations between ILO and the Russian Federation. Emphasis is placed on the currently central fields of activities of ILO. It is pointed out that the Organization is focused on the problems of decent work and job creation; eliminating child labour; gender equality; skills development; safety of work; strengthening of tripartism and social dialogue; facilitation of standards, fundamental principles and rights at work and their exercise; social justice and globalization; codification of international labour standards; cooperation with other international organizations; etc.